Kinetic Landscapes. The Cide Archaeological Project: Surveying the Turkish Western Black Sea Region - Glatz, Claudia (De Gruyter, 2015)
Turkey's northern edge is a region of contrasts and diversity. From the rugged peaks of the Pontic mountains and hidden inland valleys to the plains and rocky alcoves of the Black Sea coast, this landscape shaped and was shaped by its inhabitants' ways of life, their local cultural traditions, and the ebbs and flows of land-based and maritime networks of interaction. Between 2009 and 2011, an international team of specialists and students of the Cide Archaeological Project (CAP) investigated the challenging landscapes of the Cide and S?enpazar districts of Kastamonu province. CAP presents the first systematic archaeological survey of the western Turkish Black Sea region. The information gathered by the project extends its known human history by 10,000 years and offers an unprecedented insight into the region's shifting cultural, social and political ties with Anatolia and the Circumpontic. This volume presents the project's approach and methodologies, its results and their interpretation within period-specific contexts and through a long-term landscape perspective.